Macroscopic Carbon Nanotube Structures for Lithium Batteries. Issue 15 (29th September 2019) - Luo, Yufeng; Wang, Ke; Li, Qunqing; Fan, Shoushan; Wang, Jiaping
Abstract: Carbon nanotubes (CNTs) are regarded as one of the most promising materials to manufacture high‐performance lithium batteries. This prospect is closely related to the construction of macroscopic architectures of CNTs. The superaligned CNT (SACNT) array is a unique kind of vertically aligned CNT array. Its highly oriented feature and strong intertube force facilitate the fabrication of macroscopic SACNT structures with various forms, including unidirectional films, buckypapers, and aerogels, etc. The as‐produced SACNT macroscopic architectures are successfully introduced into lithium batteries due to their outstanding electrical and mechanical properties. Herein, an overview of the functions of macroscopic SACNTs in lithium batteries is proposed, including their applications in composite electrodes, current collectors, interlayers, and flexible full cells. Abstract : Macroscopic carbon nanotube structures, such as 2D cross‐stacked films, buckypapers, and 3D aerogels, are introduced into lithium batteries as composite electrodes, current collectors, and functional interlayers. Benefitting from their excellent electrical and mechanical properties, the cycling performance and the rate capability of the lithium batteries are effectively improved.